EARLY DOCTRINAL DEVELOPMENTS AND THE ISLAMIZATION OF MOVAROUNNAHR - Primov, Soatmurod Uralovich (Jurnal Al-Dustur, 2024)
The study of early doctrinal developments in Movarounnahr is critical for understanding the region's intellectual and theological evolution, particularly during the Islamization period. This research employs historical analysis, textual criticism, philological studies, and comparative analysis of religious doctrines to uncover the emergence and spread of theological schools such as Najjariya, Karromiya, and Moturidia. Primary sources, including chronicles, manuscripts, and inscriptions in Arabic, Persian, and Turkish, provide insights into the social, political, and intellectual contexts of the era. The findings reveal that while Bukhara was the political center, Samarkand maintained its cultural significance, preserving traditional values and fostering new theological doctrines. The spread of Abu Hanifa's teachings, brought back by scholars from Kufa, significantly influenced the Hanafi jurisprudence in regions like Balkh and Rai. Support from the Abbasid caliphs further solidified the Hanafi school's presence in Khurasan and Movarounnahr, with Samarkand and Bukhara becoming key centers of Hanafi thought. These findings underscore the importance of interdisciplinary approaches in reconstructing the intellectual landscape of early Islamic Movarounnahr.